Typology "Out of the strong came forth sweetness" - Watson, E.J. (1987)
Contents : What is typology? -- The two creations -- Noah's Ark -- The Gospel in the names of Jacob's sons -- Amazing Christian revelation in the Exodus -- The Tabernacle - a picture of Christ -- A journey through the Tabernacle -- Aaron's garments -- The altars of Israel -- The Mosaic offerings -- The annual feasts of Israel -- How to interpret the Law of Moses spiritually -- Leprosy and sin -- The camp of Israel -- Samson and the lion -- The Kinsman-Redeemer in the Book of Ruth -- Typology in the Book of Esther -- The Song of Solomon -- The story of Jonah -- The Great Priest King -- Isolated gems of typology -- Typology in John's Gospel -- Rain production: a type-picture of world evangelism. Includes diagrams.
Keywords: Bible -- criticism, interpretation, etc; Typology; Bible -- language, style